2022
DOI: 10.1155/2022/1112960
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Pulmonary Thromboembolism Based on Computer Statistical Analysis

Abstract: In order to explore the reliable clinical characteristics of patients with pulmonary thromboembolism, this paper applies computer statistical analysis methods to the analysis of clinical characteristics of patients with pulmonary thromboembolism. Moreover, starting from the actual situation, this paper combines experiments to study the case, uses sample screening and sample processing to group samples freely, and conducts grouping reliability research through data statistics methods. After verifying the reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, when endothelial cell damage or apoptosis impairscells damage or apoptosis impairs their normal anticoagulant effect, promoting thrombosis, and affecting intravascular reactive substance levels to aggravate thrombosis. 3 , 29 The importance of vascular endothelial cells necessitates investigation into mechanisms in vitro. Mechanistically, we found that NEAT1 significantly inhibited HUVECs proliferation and migration while increasing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when endothelial cell damage or apoptosis impairscells damage or apoptosis impairs their normal anticoagulant effect, promoting thrombosis, and affecting intravascular reactive substance levels to aggravate thrombosis. 3 , 29 The importance of vascular endothelial cells necessitates investigation into mechanisms in vitro. Mechanistically, we found that NEAT1 significantly inhibited HUVECs proliferation and migration while increasing apoptosis.…”
Section: Discussionmentioning
confidence: 99%